Transcriptional profiling of long noncoding RNAs and their target transcripts in ovarian cortical tissues from women with normal menstrual cycles and primary ovarian insufficiency. Issue 7 (15th May 2019) - Yao, Guidong; He, Jiahuan; Kong, Yue; Zhai, Jun; Xu, Yijiang; Yang, Guang; Kong, Deqi; Dong, Fangli; Shi, Senlin; Yang, Qingling; Sun, Yingpu
Abstract: Previous studies have shown that long noncoding RNAs (lncRNAs) show a highly tissue‐ and disease‐specific expression pattern and that they regulate the expression of neighboring genes. Because lncRNAs have been shown to be secreted into the general circulation, they may be used as diagnostic tools for some diseases. Primary ovarian insufficiency (POI) is a disease in which women have menstrual cessation before the age of 40, accompanied by elevated follicle stimulating hormone and decreased estrogen levels. In this study, ovarian cortical tissues from five women with normal menstrual cycles and from five POI patients were used for next‐generation RNA sequencing. We found 20 differentially expressed lncRNAs with 12 upregulated and eight downregulated lncRNAs in cortical tissues of POI ovaries, compared with normal controls (fold change ≥ 2 and false discovery rate[FDR] ≤ 0.05). We also found 52 differentially expressed messenger RNA transcripts, with 33 upregulated and 19 downregulated ones (foldchange ≥ 2 and FDR ≤ 0.05). Functional annotation showed that these differentially expressed transcripts were associated with follicular development and granulosa cell function. Thirteen differentially expressed lncRNAs and their targeted neighboring transcripts were coregulated in ovarian cortical tissues, including lnc‐ADAMTS1–1:1/ADAMTS1, lnc‐PHLDA3–3:2/CSRP1, lnc‐COL1A1–5:1/COL1A1, lnc‐SAMD14–5:3/COL1A1, and lnc‐GULP1–2:1/COL3A1. Furthermore, serum levels of these lncRNAs in POI patients were significantly different from those in normal patients ( p  < 0.05), and expression differences were consistent with those in ovarian cortical tissues. This study showed that key lncRNAs were differentially expressed in both ovarian cortical tissues and serum samples between women with normal menstrual cycles and POI patients. Further studies on the regulation of ovarian lncRNAs during follicular development are critical in understanding the etiologies of POI. Analyses of lncRNA expression in serum samples might provide a basis for early diagnosis and treatment of POI. Abstract : The RNA transcripts of ovarian cortical tissues in patients with primary ovarian insufficiency (POI) and normal menstrual cycles' women were analyzed using next‐generation sequencing. This is the first report regarding long noncoding RNA (lncRNA) expression in POI ovarian tissues, revealing potential roles of lncRNA in POI etiologies and providing serum lncRNA markers for POI diagnosis.